A novel bone-thinning technique for transcranial stimulation motor-evoked potentials in rats - Yuyo Maeda (Nature Portfolio, 2021)
Abstract Transcranial electrical stimulated motor-evoked potentials (tcMEPs) are widely used to evaluate motor function in humans, and even in animal studies, tcMEPs are used to evaluate neurological dysfunction. However, there is a dearth of reports on extended tcMEP recordings in both animal models and humans. Therefore, this study examined a new technique for stably recording tcMEPs over several weeks in six healthy female Sprague–Dawley rats. We thinned the skull bone using the skull base and spinal surgery technique to reduce electrical resistance for electrical stimulation. tcMEPs were recorded on days 1, 7, 14, 21, and 28 after surgery. The onset latency and amplitude of tcMEPs from the hindlimbs were recorded and evaluated, and histological analysis was performed. Stable amplitude and onset latency could be recorded over several weeks, and histological analysis indicated no complications attributable to the procedure. Thus, our novel technique allows for less invasive, safer, easier, and more stable extended tcMEP recordings than previously reported techniques. The presently reported technique may be applied to the study of various nerve injury models in rats: specifically, to evaluate the degree of nerve dysfunction and recovery in spinal cord injury, cerebral infarction, and brain contusion models.